การศึกษาแนวทางการรวมกลุ่มในการจัดการปุ๋ย เพื่อลดต้นทุนโซ่อุปทานอุตสาหกรรมปาล์มน้ำมัน กรณีศึกษาจังหวัดสุราษฎร์ธานี - วนัฐฌพงษ์ คงแก้ว (มหาวิทยาลัยสงขลานครินทร์, 2022)
Nowadays oil palm industry is one of several industries, which is important intributing Thailand's economy, and almost all of plantations are located in theof country. For the supply chain of oil palm industry, it covers four main sections includingm seeding, palm plantations, distribution centers (called Lan Tay), and crumilling plants. Based on the data from previous research, it indicated that the cost ofilizer plays the highest cost for the upstream supply chain (including palmpalm plantations). This cost is associated with logistics cost of fertilizer transportation startingfrom fertilizer factories or warehouses (distributed by their agents) to oil palm smallholderfarmers.This research was conducted to study and develop the oil palm smallholderfarmers' collaboration in fertilizer management, covering procurement and purchasing,inventory management, and material shipping and distribution, in order to meet thedemands of palm plantations and to reduce supply chain costs for the oil palm industry inSura Thani province. The transshipment model incorporated with the set covering problemand the Premium Solver Platform software were used to find the optimal model for thelder farmers' collaboration in fertilizer management. According toing, it was divided into two stages: The first stage was to determine theishing the collaborative group of smallholder farmers to manage anr its own members under the limitation of distance. The second stageof the first stage to analyze the total logistics costin fertilizer ithroughout the supply chain. The result showed that the optimal group for the oil palmlholder farmers' collaboration must be established in a total of 50 groudistribution to their own members within 10 kilometers. Consequently,logistics cost in supply chain was reduced from 153,172,432.54 baht per year (estimated bye current model) to 88,314,504.61 baht per year, or decreased by 42.34%